Viral Kinetics and Resistance Development in Children Treated with Neuraminidase Inhibitors: The Influenza Resistance Information Study (IRIS). (27th September 2019) - Roosenhoff, Rueshandra; Reed, Vaughan; Kenwright, Andy; Schutten, Martin; Boucher, Charles A; Monto, Arnold; Clinch, Barry; Kumar, Deepali; Whitley, Richard; Nguyen-Van-Tam, Jonathan S; Osterhaus, Albert D M E; Fouchier, Ron A M; et al.
Abstract: Background: We studied the effect of age, baseline viral load, vaccination status, antiviral therapy, and emergence of drug resistance on viral shedding in children infected with influenza A or B virus. Methods: Samples from children (aged ≤13 years) enrolled during the 7 years of the prospective Influenza Resistance Information Study were analyzed using polymerase chain reaction to determine the influenza virus (sub-)type, viral load, and resistance mutations. Disease severity was assessed; clinical symptoms were recorded. The association of age with viral load and viral clearance was examined by determining the area under the curve for viral RNA shedding using logistic regression and Kaplan-Meier analyses. Results: A total of 2131 children infected with influenza (683, A/H1N1pdm09; 825, A/H3N2; 623, influenza B) were investigated. Age did not affect the mean baseline viral load. Children aged 1−5 years had prolonged viral RNA shedding (±1–2 days) compared with older children and up to 1.2-fold higher total viral burden. Besides, in older age (odds ratio [OR], 1.08; confidence interval [CI], 1.05–1.12), prior vaccination status (OR, 1.72; CI, 1.22–2.43) and antiviral treatment (OR, 1.74; CI, 1.43–2.12) increased the rate of viral clearance. Resistance mutations were detected in 49 children infected with influenza A virus (34, A/H1N1pdm09; 15, A/H3N2) treated with oseltamivir, most of whom were aged <5 years (n = 39). Conclusions: Children aged 1−5 years had a higher total viral burden with prolonged virus shedding and had an increased risk of acquiring resistance mutations following antiviral treatment. Clinical Trials Registration: NCT00884117. Abstract : We demonstrate that children aged 1−5 years shed a 1.04- to 1.24-fold higher total quantity of influenza virus compared with older children associated with an increased risk of acquiring resistance mutations following antiviral treatment.